The Influence of Cash Turnover and Receivables Turnover on the Profitability of the Mining Sub Sector Listed on the Indonesian Stock Exchange Period 2019 – 2023 - Wel Mau, Rio Anseda; Mulyani, Sri; Nuridah, Siti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to examine the effect of Cash Turnover and Receivables Turnover on Profitability. The population used in this research consists of all mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. This research employs a quantitative method. The sampling method used is purposive sampling, based on specific criteria that have been determined. The total population of mining companies is 81, and after applying the sampling criteria, 11 companies were selected, resulting in 55 samples over a five-year period. The data used in this study is secondary data in the form of financial statements obtained from the website www.idx.co.id and from each company’s respective website. The analytical technique employed in this study is multiple linear regression analysis, using IBM SPSS 26 software. The results of the study indicate that Cash Turnover does not have an effect on Profitability. The results for Receivables Turnover show that it does not have an effect on Profitability. However, the simultaneous results indicate that both Cash Turnover and Receivables Turnover have a significant effect on Profitability.